Tribocatalysis mechanisms: electron transfer and transition - Li, Xinnan; Tong, Wangshu; Shi, Jing; Chen, Yunfan; Zhang, Yihe; An, Qi (Journal of materials chemistry. A, Materials for energy and sustainability, 2023)
Tribocatalysis is an emerging technology that can convert mechanical energy into chemical energy to degrade organic pollutants. The two widely used tribocatalysis mechanisms are the electron transfer and transition mechanisms. Currently, there is no definitive criterion to determine which mechanism is best employed for proper implementation in a tribocatalysis reaction. In this review, research that compares the two mechanisms through their electronic structures as criteria for selection is discussed. The factors influencing the tribocatalysis performance as well as criteria for tribocatalysis mechanism selection are the surface state, energy band structure, and force. Finally, the proposed standard method to analyze the electronic state, relation between the catalyst and H 2 O (O 2 ), energy band bending theory, and charge preservation for tribocatalysis must be explored for tribocatalysis mechanism development. This review seeks to elicit meaningful discussion for distinguishing the unique characteristics of the two existing mechanisms and understanding the details of tribocatalysis mechanisms. The differences between the two mechanisms of tribocatalysis are compared, and the selection criteria for a specific reaction are given.